Single‐nucleotide polymorphisms of two closely related microsporidian parasites suggest a clonal population expansion after the last glaciation. Issue 2 (19th November 2012) - Haag, Karen L.; Traunecker, Emmanuel; Ebert, Dieter
Abstract The mode of reproduction of microsporidian parasites has remained puzzling since many decades. It is generally accepted that microsporidia are capable of sexual reproduction, and that some species have switched to obligate asexuality, but such process had never been supported with population genetic evidence. We examine the mode of reproduction of Hamiltosporidium tvaerminnensis and Hamiltosporidium magnivora, two closely related microsporidian parasites of the widespread freshwater crustacean Daphnia magna, based on a set of 129 single‐nucleotide polymorphisms distributed across 16 genes. We analyse 20 H. tvaerminnensis isolates from localities representative of the entire species' geographic distribution along the Skerry Island belt of the Baltic Sea. Five isolates of the sister species H. magnivora were used for comparison. We estimate the recombination rates in H. tvaerminnensis to be at least eight orders of magnitude lower than in H. magnivora and not significantly different from zero. This is corroborated by the higher divergence between H. tvaerminnensis alleles (including fixed heterozygosity), as compared to H. magnivora. Our study confirms that sexual recombination is present in microsporidia, that it can be lost, and that asexuals may become epidemic.